Dampak Judi Online terhadap Kehidupan Masyarakat di Kelurahan Madawat Kecamatan Alok Kabupaten Sikka - Natalis, Stevanus; Aswim, Danar; Wahab, M. Ihsan (Universitas Syiah Kuala, 2025)
This research is motivated by the rampant online gambling activities among the people of Madawat Village. Therefore, the researcher conducted this research with the aim of determining the impact of online gambling on the lives of the people in Madawat Village, Alok District, Sikka Regency. The method used in this research is a qualitative approach. Data sources consist of primary and secondary data. Primary data sources include residents of Madawat Village and the local government of Madawat Village, while secondary data sources consist of books, mass media, and other references related to online gambling. Data collection techniques include observation, interviews, and documentation. Data analysis follows the following stages: data presentation, data reduction, drawing conclusions, and verification. The expected output is a scientific article published in a socio-cultural journal.